Anxiety and depression in healthcare workers are associated with work stress and poor work ability - Nicola Magnavita; Igor Meraglia; Matteo Riccò (AIMS Public Health)
BackgroundSymptoms of anxiety and depression are very common among healthcare workers (HCWs) and could impact the quality of care.ObjectiveThis study aimed to evaluate the prevalence of these disorders in a public health company and their association with work ability and work-related stress.MethodsA cross-sectional study involved 80 HCWs being treated for mental disorders (MD), 55 HCWs who said they suffered from MD but were not being treated, and 824 healthy colleagues. All workers completed the Work Ability Index (WAI), the Siegrist's Effort/Reward Imbalance questionnaire (ERI), the Goldberg's scales of anxiety and depression (GADS), and the Warr's scale of job satisfaction.ResultsThree-quarters of workers with MD suffered from anxiety and/or depression. Workers who declared at the periodic medical examination in the workplace that they were being treated for MD had significantly lower levels of work ability than those of their colleagues who declared good mental health. They also reported greater work stress (high effort, low rewards, high overcommitment) and lower job satisfaction than their healthy colleagues. Symptomatic but untreated workers reported significantly lower work ability, lower satisfaction, and greater occupational stress than their healthy colleagues. In the entire sample, there were many workers with symptoms of anxiety or depression who did not declare these disorders during the examination. Overall, there were 328 suspected cases of anxiety (34.2%) and 334 cases of depression (34.8%). Anxious workers [OR = 8.11, 95% confidence interval (CI) = 3.74–17.58] and depressed workers (OR = 4.49, 95% CI = 2.22–9.10) had an increased risk of being classified as having “poor work ability”.ConclusionThe negative association between psychological symptoms and work ability even in undiagnosed/untreated workers demonstrates the usefulness of screening for these symptoms in work environments.